Nanoscale Materials and Devices for Electronics, Photonics and Solar Energy - Korkin, Anatoli; Goodnick, Stephen; Nemanich, Robert (Nanostructure Science and Technology, 2015)
This book presents research dedicated to solving scientific and technological problems in many areas of electronics, photonics and renewable energy. Progress in information and renewable energy technologies requires miniaturization of devices and reduction of costs, energy and material consumption. The latest generation of electronic devices is now approaching nanometer scale dimensions; new materials are being introduced into electronics manufacturing at an unprecedented rate; and alternative technologies to mainstream CMOS are evolving. The low cost of natural energy sources have created economic barriers to the development of alternative and more efficient solar energy systems, fuel cells and batteries. Nanotechnology is widely accepted as a source of potential solutions in securing future progress for information and energy technologies. Nanoscale Materials and Devices for Electronics, Photonics and Solar Energy features chapters that cover the following areas: atomic scale materials design, bio- and molecular electronics, high frequency electronics, fabrication of nanodevices, magnetic materials and spintronics, materials and processes for integrated and subwave optoelectronics, nanoCMOS, new materials for FETs and other devices, nanoelectronics system architecture, nano optics and lasers, non-silicon materials and devices, chemical and biosensors,quantum effects in devices, nano science and technology applications in the development of novel solar energy devices, and fuel cells and batteries.